FTIR and Raman Spectroscopy Study of Soot Deposits Produced in the Infrared Multiphoton Dissociation of Vinyl Bromide - Samoudi, B.; Bendaou, O.; Hanafi, I.; Asselman, A.; Haboubi, K. (Journal of Spectroscopy, 2022)
Even at low concentrations, poly-aromatic hydrocarbons found in soot have substantial health implications. Soot deposits have been reported and studied using FTIR and Raman spectroscopy. Using a CO2 photolysis laser, the samples were obtained via infrared multiphoton dissociation (IRMPD) of vinyl bromide (VBr, C2H3Br) molecules. The solid deposit formed in the IRMPD of VBr when a relatively high fluence of the order of 204 J.cm−2 was analyzed by FTIR, and it was discovered that the majority of its composition is aromatic and aliphatic hydrocarbons. Significant fullerene-type carbonaceous soot particles are also found, which could correspond to C60 and C70 or other carbonaceous agglomerates of a higher order; however, the disappearance of this fullerene on Raman spectra cast doubt on this explanation. Our samples’ Raman spectroscopy has been compared to Tamor and Vassell’s research, which may indicate that they have a lesser degree of hardness and density than these authors’ results, indicating a larger hydrogen content in our samples. The optical gap has been calculated, yielding a very limited range of values ranging only between 1.0 and 1.2 eV, resulting in a crystalline size of 0.58 to 1.12 nm.